2020
DOI: 10.30957/ijoltl.v5i1.612
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis on Interlanguage Fossilization in Students’ Writing Performance

Abstract: This present study tries to investigate the students’ writing performance to know whether interlanguage fossilization is occurring or not. The primary goal of this research is to give information relating to interlanguage fossilization in students’ writing performance of the English Education Study Program of IAIN JuraiSiwo Metro. This research is qualitative research. It is used to describe interlanguage fossilization that occurred in students’ writing performance. The writer uses observation, documentation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…The main objectives of this paper are (1) to analyze the causes of fossilization as well as to analyze the current situation of language learning; (2) to analyze the causes of fossilization through examples further; and (3) to suggest some strategies and recommendations that can be used to avoid and prevent fossilization.…”
Section: Research Objectivementioning
confidence: 99%
See 2 more Smart Citations
“…The main objectives of this paper are (1) to analyze the causes of fossilization as well as to analyze the current situation of language learning; (2) to analyze the causes of fossilization through examples further; and (3) to suggest some strategies and recommendations that can be used to avoid and prevent fossilization.…”
Section: Research Objectivementioning
confidence: 99%
“…First, lexical includes both real and imaginary words. Nouns involve singular and plural changes, and coronals do not exist in Chinese, so in English writing, learners often make mistakes in using these words [1]. In addition to the misuse of the crown and countable and uncountable nouns, confusion of word properties, abuse of transitive and intransitive verbs, misuse of modal verbs, and confusion between regular and irregular changes of verbs in the past tense and past participle are also common errors in English writing [4].…”
Section: Grammarmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, IL is unique since there is a gap that allows the students' linguistic system to stay in the middle of L1 and L2 rules. Further still, Ellis & Barkhuizen (2005) in Fauziati (2016) highlighted some IL characteristics as follows: (1) systematic, it refers to the internal consistency of rule and feature which shape IL; (2) dynamic, it deals with interim grammar resulted from the frequent change on students' system of rules in mind; (3) variable, it occurs when students 85 employ a range of form of grammatical structure at development stage; IL produces (4) learning strategies; (5) fossilization, it points potential errors which can cause permanent effects on students' second language and; (6) it permeable to infiltration by L1 and L2 rules.…”
Section: Introductionmentioning
confidence: 99%
“…The result showed that the IL of the learners triggered by a developmental process. The third study by Aini, et al (2020) In Indonesia, English is widely used and currently becomes a chosen language learned referring to the curriculum of 2013. According to Dardjwidjojo (Endriyani & Anggraeni, 2019), it was first introduced as local content in primary school in 1994.…”
Section: Introductionmentioning
confidence: 99%